Influences of semiconductor oxide fillers on the corrosion behavior of metals under coatings. (1st December 2018) - Li, Sijia; Sun, Wen; Yang, Zhengqing; Zhang, Xinyu; Wang, Lida; Liu, Guichang
Abstract: Semiconductor oxides are widely used as coating fillers, while few studies have focused on the interactions between semiconductor fillers and metal substrates. In this paper, common semiconductor fillers including TiO2, Fe2 O3 and Cu2 O were prepared and incorporated into polyvinyl butyral coatings. Localized EIS, EIS, SEM and electrochemical noise analysis were applied to study the corrosion behavior of semiconductor/metal contacts at coating defects. Results revealed that TiO2 and Fe2 O3 accelerated the corrosion of metals, while Cu2 O showed no promising effect. Meanwhile, a micro-galvanic corrosion mechanism based on work function difference and oxygen reduction reaction activity was proposed to explain the corrosion-promotion phenomenon.